2017
DOI: 10.4196/kjpp.2017.21.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin induces apoptosis and cell cycle arrest in triple-negative breast cancer cells through modulation of Foxo3a activity

Abstract: Quercetin, a plant-derived flavonoid found in fruits, vegetables and tea, has been known to possess bioactive properties such as anti-oxidant, anti-inflammatory and anti-cancer. In this study, anti-cancer effect of quercetin and its underlying mechanisms in triple-negative breast cancer cells was investigated. MTT assay showed that quercetin reduced breast cancer cell viability in a time and dose dependent manner. For this, quercetin not only increased cell apoptosis but also inhibited cell cycle progression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 49 publications
7
91
0
2
Order By: Relevance
“…The antitumor properties of flavonoids are discussed in the literature [21][22][23]. The data obtained by us are consistent with the results of other authors demonstrating that flavonoids activate apoptosis in tumor cells [24,25], while not having toxicity. Thus, it is known that the flavonoid Vogonin as part of the popular Chinese herbal remedy Huang-Qin (based on grass skullcap Baikal) induces apoptosis in a wide range of human tumor cells in vitro and inhibits tumor growth in vivo in various models of mouse tumors [3,[29][30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 90%
“…The antitumor properties of flavonoids are discussed in the literature [21][22][23]. The data obtained by us are consistent with the results of other authors demonstrating that flavonoids activate apoptosis in tumor cells [24,25], while not having toxicity. Thus, it is known that the flavonoid Vogonin as part of the popular Chinese herbal remedy Huang-Qin (based on grass skullcap Baikal) induces apoptosis in a wide range of human tumor cells in vitro and inhibits tumor growth in vivo in various models of mouse tumors [3,[29][30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 90%
“…Contradictory results on the cell population percentage altered with quercetin were also reported in these studies, where higher G2/M cell population after quercetin administration was reported [22,30], while two different investigations found a decrease in this phase of the cell cycle [39,49]. Similarly, one study determined that quercetin-derived cell cycle detention was in S and G2/M phases in MDA-MB-231 breast cancer line [66] in contrast to the G0/G1 phase arrest observed in MCF-7 breast cancer cell line [65]. This variable role of quercetin on cell cycle regulation has also been shown in cells models of non-small cell lung cancer [64] and breast cancer [65,66], and enhanced through its combination [68], encapsulation [69], as well as with quercetin derivatives [71].…”
Section: Discussionmentioning
confidence: 56%
“…Results presented in this article collect a great variety of antitumor actions of either quercetin or the mentioned strategies of combination, encapsulation and derived compounds. Cell growth inhibition, in addition to apoptosis stimulation, were the main processes described as quercetin mechanisms of action against HCC, properties that have also been observed in different tumors, such as non-small cell lung cancer [64] and breast cancer [65,66]. Although almost studies associated antiproliferative activity of quercetin with alteration of several pathways, Akt/mTOR and MEK1/ERK1/2 signaling routes were mostly found to be regulated by this flavonoid, either as free drug as well as encapsulated [23,24,27,38,42].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although Triple negative breast cancer accounts for only 15% of other breast cancer subtypes, it shows high rate of recurrence and develops resistance to chemotherapy as previously reported by (Rakha et al, 2008). In addition, patients have shown poor prognosis due to the lack of specific targeted therapy (Nguyen et al, 2017). Therefore, it is vital to look for new therapeutic agents that are effective, less toxic and can prevent relapse emergence.…”
Section: Introductionmentioning
confidence: 94%